An empirical and descriptive study of the translation method for dubbing and subtitling - Martí Ferriol, José Luis (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
An Empirical and Descriptive Study of the Translation Method for Dubbing and Subtitling is the title of a doctoral thesis submitted in November 2006. This research project developed a theoretical framework where the notion of translation method was defined in terms of a graphical and parametrical representation as a function of three parameters: constraints active in audiovisual translation, translation norms and translation techniques. The object of study consisted of several independent American films shown in Spain, in dubbed and subtitled versions, in the period between 2001 and 2004. Both the preliminary and the translation phases of the translation process were taken into account in the scope of work. Empirical data were gathered through interviews with the translators of the films for the preliminary phase of the translation process; the compilation of almost 500 micro textual samples of the two translated versions provided the empirical data for the translation phase itself. The results and conclusions of the study were obtained by using rigorous statistical tools, which showed the similarities and differences between the translation methods for both the dubbed and the subtitled versions.